(untitled) (Health Renaissance, 2012)
Nonpuerperal uterine inversion is a rare condition. We describe a case report of chronic inversion secondary to submucous fibroid. A 37 years lady presented with acute retention of urine with submucous fibroid. Diagnosis of partial inversion was made intra operatively and she underwent abdominal hysterectomy. Health Renaissance; September-December 2012; Vol 10 (No.3);242-2431 DOI: http://dx.doi.org/10.3126/hren.v10i3.7055